Chemical restraint of adults with intellectual disability and challenging behaviour in Queensland, Australia: Views of statutory decision makers. (June 2020) - Edwards, Nicole; King, Julie; Williams, Karen; Hair, Sara
Background: Psychotropic medication is widely prescribed to treat mental illness. However, it is controversial when used as a chemical restraint (CR) to manage challenging behaviours (CBs) of adults with intellectual disability (ID). CR has potentially negative consequences and affects human rights. Method: Qualitative research conducted between 2014 and 2015 explored the views of 'guardian' decision makers appointed under unique Queensland legislation oversighting the use of CR. Results: Findings included (1) negative conceptualization of CR, (2) concerning relationships with prescribers and disability sector staff, (3) challenges to information seeking about people with ID prescribed CR and (4) problematic implementation of positive behaviour support plans. Conclusion: According to guardians, CR may be used in lieu of community supports, and prescribers sometimes diagnose mental illness to avoid CR legislative requirements. Guardians, prescribers and professionals would benefit from training that addresses the intersection between physical and mental health, CB and CR.